2022
DOI: 10.1186/s12967-022-03341-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin increases bone mass in normal, perimenopausal, and postmenopausal osteoporotic rats via the promotion of osteogenesis

Abstract: Background Osteoporosis is a disease threatening the health of millions of individuals. Melatonin is found to be a potential anti-osteoporosis drug. However, whether melatonin plays a role against osteoporosis at different stages of the menopause and the underlying mechanisms are unknown. Methods Ovariectomy was utilized as a model of perimenopausal and postmenopausal osteoporosis. A total of 100 mg/kg melatonin, or solvent alone, was added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…The size distribution of most exosomes ranged from 50 to 120 nm (Fig. 2 C), which was consistent with other reports [ 15 , 28 ]. The data indicated that the microvesicles derived from BMSCs were successfully obtained, and were predominantly exosomes.…”
Section: Resultssupporting
confidence: 92%
“…The size distribution of most exosomes ranged from 50 to 120 nm (Fig. 2 C), which was consistent with other reports [ 15 , 28 ]. The data indicated that the microvesicles derived from BMSCs were successfully obtained, and were predominantly exosomes.…”
Section: Resultssupporting
confidence: 92%
“…The size distribution of most exosomes ranged from 50 nm to 120 nm (Fig. 2C), which was consistent with other reports [14,23]. The data indicated that the microvesicles derived from BMSCs were successfully obtained, and were predominantly exosomes.…”
Section: Characterization Of Bmscs and Bmscs-exossupporting
confidence: 91%
“…Kobayashi-Sun et al [138] reported that melatonin inhibits the differentiation of both osteoblasts and osteoclasts in the zebrafish scale because it prevents the Erk signaling cascade. These results contrast with those obtained in the in vitro model of mammalian cells, and also in vivo in which melatonin increases bone formation [139]. This negative effect of melatonin on osteoblasts has also been seen when incubated with osteoclasts [140].…”
Section: Regulation Of Bone Metabolism By Melatonin In Zebrafishcontrasting
confidence: 90%